Leishmania major UDP-sugar pyrophosphorylase salvages galactose for glycoconjugate biosynthesis. Issue 12 (October 2015) - Damerow, Sebastian; Hoppe, Carolin; Bandini, Giulia; Zarnovican, Patricia; Buettner, Falk F.R.; Ferguson, Michael A.J.; Routier, Françoise H.
Graphical abstract: Highlights: Galactose salvage in Leishmania major is mediated by UDP-sugar pyrophosphorylase (USP). USP is not rate limiting for glycocalyx biosynthesis under standard growth conditions. Salvage by USP contributes to glycoconjugate biosynthesis but is insufficient on its own. Abstract: Leishmaniases are a set of tropical and sub-tropical diseases caused by protozoan parasites of the genus Leishmania whose severity ranges from self-healing cutaneous lesions to fatal visceral infections. Leishmania parasites synthesise a wide array of cell surface and secreted glycoconjugates that play important roles in infection. These glycoconjugates are particularly abundant in the promastigote form and known to be essential for establishment of infection in the insect midgut and effective transmission to the mammalian host. Since they are rich in galactose, their biosynthesis requires an ample supply of UDP-galactose. This nucleotide-sugar arises from epimerisation of UDP-glucose but also from an uncharacterised galactose salvage pathway. In this study, we evaluated the role of the newly characterised UDP-sugar pyrophosphorylase (USP) of Leishmania major in UDP-galactose biosynthesis. Upon deletion of the USP encoding gene, L. major lost the ability to synthesise UDP-galactose from galactose-1-phosphate but its ability to convert glucose-1-phosphate into UDP-glucose was fully maintained. Thus USP plays a role in UDP-galactose activation but does not significantly contribute to the de novo synthesis of UDP-glucose. Accordingly, USP was shown to be dispensable for growth and glycoconjugate biosynthesis under standard growth conditions. However, in a mutant seriously impaired in the de novo synthesis of UDP-galactose (due to deficiency of the UDP-glucose pyrophosphorylase) addition of extracellular galactose increased biosynthesis of the cell surface lipophosphoglycan. Thus under restrictive conditions, such as those encountered by Leishmania in its natural habitat, galactose salvage by USP may play a substantial role in biosynthesis of the UDP-galactose pool. We hypothesise that USP recycles galactose from the blood meal within the midgut of the insect for synthesis of the promastigote glycocalyx and thereby contributes to successful vector infection.